THE ROLE OF INFORMATION TECHNOLOGY AND CREATIVITY IN ACHIEVING BUSINESS SUSTAINABILITY - Widiastuti, Ekaningtyas; Sulistyandari, Sulistyandari (Transpublika Publisher, 2024)
This research investigates how information technology and creativity contribute to the sustainability of businesses run by students enrolled in the Student Entrepreneurship Program at Universitas Jenderal Soedirman. To gather empirical data, a structured questionnaire was administered to 100 entrepreneurial students participating in the program. The sample was selected using convenience sampling, a method often employed in exploratory research to quickly gather relevant data from a readily accessible population. The collected data was subjected to rigorous statistical analysis using the SPSS software, specifically employing the Multiple Linear Regression method to ascertain the relationship between the independent variables (information technology and creativity) and the dependent variable (business sustainability). The results of the analysis revealed a significant positive impact of both information technology and creativity on the sustainability of student-run businesses. Information technology, with its ability to streamline operations, enhance communication, and provide access to broader markets, emerged as a crucial factor in ensuring business continuity and growth. Concurrently, creativity was identified as a key driver of innovation, enabling businesses to adapt to changing market conditions and develop unique value propositions. In light of these findings, the study underscores the importance of optimizing the use of information technology and fostering a creative mindset among student entrepreneurs. To enhance business performance and sustainability, it is recommended that educational institutions and policy-makers support initiatives that provide students with access to cutting-edge technological tools and encourage creative problem-solving.